Racial Discrimination in Ta-Nehisi Coates’s Between the World and Me - Angger Cahya Ardinang; Anik Cahyaning Rahayu (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This study is about racial discrimination in Ta-Nehesi Coates’s Between the World and Me. The objective of this study is to describe the types and effects of racial discrimination experienced by Ta-Nehesi Coates’s and black people in the novel. Descriptive qualitative method is used as the research method. This study uses an sociology approach. To analyze racial discrimination, the writer uses Fred L. Pincus theory. Chen and Mallory's theory of the impact of racial discrimination is used to analyze the impact experienced by Coates and black people. There are two types of racial discrimination that occur, namely individual and institutional discrimination. Individual discrimination includes racial prejudice and acts of violence, while institutional discrimination occurs in the fields of education and law. Meanwhile, there are two types of impact on Ta-Nehesi Coates’s and black people as victims of racial discrimination. The first is the impact on mental health, Coates feels fear, anger and anxiety. The second is the impact on physical health, in the novel it is only mentioned that the racial discrimination experience by Coates resulted in dizziness and vertigo. In the novel, it is found that individual and institutional forms of racial discrimination can have an impact on mental and physical health.